2013
DOI: 10.1111/jasp.12181
|View full text |Cite
|
Sign up to set email alerts
|

Passion and challenging goals: drawbacks of rushing into goal‐setting processes

Abstract: This study shows that passion may have a potential downside for setting challenging goals. Hypotheses are developed by drawing on self‐determination theory and goal‐setting theory. Data is collected from a sample of 134 team leaders and hypotheses are tested using ordinary least squares regression analyses. Findings demonstrate that in a project context, team leaders' own competence positively influences their obsessive passion, while their perceptions of team members' competence positively influence their har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…Unlike outcomes of work passion, its antecedents are less well understood, with the majority of studies examining the predictive validity of individual characteristics. For instance, employees' confidence was found to be positively related to harmonious passion but not to obsessive passion (Thorgren & Wincent, 2013), and autonomy personality orientation, which allows freedom in pursuing one's actions and goals, predicted harmonious passion (Liu et al, 2011; Vallerand et al, 2006), whereas controlled personality orientation predicted obsessive passion (Vallerand et al, 2006). The role of situational influences has received less attention, but preliminary evidence indicates that harmonious passion is facilitated in the presence of job autonomy (Fernet, Lavigne, Vallerand, & Austin, 2014) and cooperative psychological climate (Ho et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Unlike outcomes of work passion, its antecedents are less well understood, with the majority of studies examining the predictive validity of individual characteristics. For instance, employees' confidence was found to be positively related to harmonious passion but not to obsessive passion (Thorgren & Wincent, 2013), and autonomy personality orientation, which allows freedom in pursuing one's actions and goals, predicted harmonious passion (Liu et al, 2011; Vallerand et al, 2006), whereas controlled personality orientation predicted obsessive passion (Vallerand et al, 2006). The role of situational influences has received less attention, but preliminary evidence indicates that harmonious passion is facilitated in the presence of job autonomy (Fernet, Lavigne, Vallerand, & Austin, 2014) and cooperative psychological climate (Ho et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[Omorede, Thorgren and Wincent] () found that a leader's obsessive passion is affected by his or her competence for the task and the project team's task competence. [Thorgren and Wincent] () conducted a study on how project leaders' passion determines how quickly the leader and his or her team develop and establish team goals. They find that setting goals quickly may eventually be somewhat problematic; indeed, such rapid actions may result in setting less ambitious goals.…”
Section: Discussion Future Research and Conclusionmentioning
confidence: 99%
“…Harmonious passion, on the other hand, is positively related to subjective well‐being (Rousseau and Vallerand, ) and positive affect (Stoeber et al ., ), and improves learning and the ability to incorporate feedback (Lavigne, Forest and Crevier‐Braud, ). Although obsessive passion and harmonious passion both require active and rapid engagement in activities (Thorgren and Wincent, ), the mode of passion – harmonious or obsessive − may be more or less conducive to situations leaders face.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vallerand et al (2003) defined harmonious passion as a type of passion for an activity that is in harmony with other aspects of life and this results from the autonomous internalisation of a favourite activity into one's identity. Such type of passion develops in the individuals when they devote time and energy to their activities (Thorgren & Wincent, 2013). Although most research on harmonious passion has been conducted in sports and other activities in the past with positive outcomes, the topic has been generating interest among scholars in the organisational context Ma et al, 2018).…”
Section: Cooperative Psychological Climate and Harmonious Passionmentioning
confidence: 99%